The Patterns of Possibility - How to Recast Relationships to Create He althier Systems and Better Outcomes - Winhall, Jennie; Leadbeater, Charles (The Rockwool Foundation, 2022)
In Building Better Systems, we introduced four keys to unlock system i nnovation: purpose and power, relationships and resource flows. These four keys make up a set. Systems are often hard to change because powe r, relationships, and resource flows are locked together in a reinforc ing pattern to serve the system’s current purpose. Systems start to ch ange fundamentally when this pattern is disrupted and opened up so tha t a new configuration can emerge, serving a new purpose. In this artic le series we delve deeper into these four keys and provide practical a dvice on how they can be put to use. This article is about relationshi ps. Systems are defined by the patterns of interactions between their parts: their relationships. Those interactions generate the outcomes o f the system as a whole. Transforming the outcomes of a system require s remaking its relationships and then unlocking the other keys to syst em innovation: purpose, power and resources. This shift in relationshi ps allows all those in the system to learn faster, to be more creative . System innovators redesign the relationships in the system to allow dramatically enhanced learning across the system, and thereby generate far better outcomes.